REGIONAL FINANCIAL MANAGEMENT SYSTEM OF REGENCY/CITY REGIONAL ORIGINAL INCOME IN ACEH PROVINCE PERIOD YEAR 2016-2020 - Bustani, Bustani; Khaddafi, Muammar; Nur Ilham, Rico (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to examine the effect of general allocation funds, special allocation funds and profit-sharing funds on local revenue in districts/cities in Aceh Province . This study uses secondary data, namely data obtained from the report on the realization of the district/city APBD in Aceh Province from 2016-2020 by accessing the official website on the website of the Directorate General of Fiscal Balance and the Regional Finance Agency of Aceh Province. The data analysis technique was using panel data regression analysis. The results of the analysis in this study indicate that the general allocation fund has a positive and significant effect on regional original income and the special allocation fund has a negative and significant effect on regional original income, while profit sharing funds have a significant negative effect on regional original income.